Improving menopausal symptoms and reducing depression in postmenopausal women: Effectiveness of transferring experiences in group education - Shervin-Sadat Hashemian; Soghra Masom-Alipour; Arash Najimi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: One of the most critical stages of women's lives is menopause. Meanwhile, group training can have a significant effect on reducing menopausal symptoms. The aim of this study was to investigate the effectiveness of group training on reducing menopausal symptoms in postmenopausal women. METHODS: This study was a randomized controlled trial. The study population was 96 postmenopausal women visiting health centers in the city of Shazand (Markazi Province, Iran). Data collection tools in this study were the Menopausal Rating Scale Questionnaire and the Beck Depression Inventory. Group training intervention consisted of four training sessions. The duration of each session was 2 h. The questionnaires were completed in two stages of pre- and post-test (8 weeks later) for the intervention and control groups. Data were analyzed using descriptive statistics (absolute and relative frequency, mean and standard deviation) and analytical statistics (independent t-test, paired t-test, and analysis of covariance). RESULTS: The mean age in the intervention group and the control group was 49.93 ± 3.44 and 51.66 ± 2.93 years, respectively. In the intervention group, the mean menstrual time was 2.37 ± 167 years and in the control group, the mean time elapsed from the last menstrual period was 3.91 ± 2.68 years. The mean scores of menopausal physical symptoms (F = 58.69), menopausal symptoms (F = 43.45), menopausal urinary and genital symptoms (F = 33.50), and depression (F = 58.25) had a significant decrease in intervention group, while in the control group, these changes were not significant (P < 0.001). CONCLUSION: Regarding the findings of this study, which indicates the effect of group training program on the improvement of physical, psychological, urinary and genital symptoms, and menopausal depression, it seems that group training in menopause can be an effective method.